ANALYSIS OF THE OPERATION OF THE BLADES OF THE SKATING RINK – CHOPPER IN THE CONDITIONS OF ITS ROLLING ON THE GROUND - Sheichenko, V.; Volskyi, V.; Kotsiubanskyi, R.; Skoriak, Y.; Priliepo, N. (Scientific Progress & Innovations, 2022)
One of the most promising ways of solving the problem of quality of the technological process of interaction of knives with the vegetative-soil environment is a theoretical analysis of grinder roller blade work under the conditions of its rolling on the soil. The quality of work of grinder roller largely depends on the correct choice of their rational parameters and modes of operation, which are completely determined not only by its design features, but also operating conditions. The process of interaction of the grinder roller blade with the vegetative-soil environment was investigated by an analytical method. It is noted that under conditions when the number of rows of knives in the roller design and their parameters allow approximately the same value of the length of the circle between the tips of the knives with its height (maximum value of immersion depth of the knife in the soil environment), there is a variant of center and lifting. This is possible when the contact with the soil environment is continuous. The noted features of the movement of the center C will take place both at a small depth of immersion of knives in the plant-soil environment, and at significant depth values. The influence of the angle β (the angle between the velocity vector of the point K and the vertical) on the conditions of penetration of the knife into the plant-soil environment is established. Under the conditions of coincidence of the direction of installation of the knife with the radius of the drum, dependence was established, according to which the influence on the angle β of design parameters (drum radius б r , knife width Н h , angle  ) and technological parameter 1 h , which determines the distance from the point K to the horizontal line of the greatest penetration of knives into the plant-soil environment. Under the conditions of displacement by the angle   of the direction of installation of the knives relative to the radius of the drum of the roller in the direction coinciding with the direction of rotation of the drum, the dependence, according to which the influence on the angle β' (the angle between the vertical and the direction of the speed of the end point of the knife K'), design parameters (drum radius б r , knife width Н h , angles  and   ), as well as the technological parameter 1 h , which determines the distance from the point К' to the horizontal line of the greatest penetration of knives into the plant-soil environment.